Armed struggle and the search for state : the Palestinian national movement, 1949-1993 - Ṣāyigh, Yazīd (Clarendon Press ; Oxford University Press, 1997)
"Based on unprecedented access to PLO archives and personnel, this groundbreaking new study represents the definitive history of the Palestinian national movement. Spanning the 45 years from the establishment of the State of Israel in 1948 to the PLO-Israel accord of 1993, it sheds radical new light on the history of the Middle East in the last half of the twentieth century. This masterly new work spans an entire epoch in the history of the contemporary Palestinian national movement, from the establishment of Israel in mandate Palestine in 1948, to the PLO-Israel accord of 1993. Contrary to the conventional view that national liberation movements proceed with state-building only after attaining independence, the case of the PLO shows that state-building may shape political institutionalization throughout the previous struggle, even in the absence of an autonomous territorial, economic, and social base. That is the central argument of this insightful study, which traces the political, ideological, and organizational evolution of the PLO and its constituent guerrilla groups. Taking the much-vaunted 'armed struggle' as its connecting theme, it shows how conflict was used to mobilize the mass constituency, assert particular discourses of revolution and nationalism, construct statist institutions, and establish the legitimacy of a new political class and bureaucratic elite. The book draws extensively on PLO archives, official publications and internal documents of the various guerilla groups, and over 400 interviews conducted by the author with the PLO rank-and-file. Its span, primary sources, and conceptual framework make this the definitive work on the subject"--Provided by publisher